"Nature's child" and "the diplomat": A cross-case study of the emotional adjustment strategies of two gifted students. (September 2018) - Haberlin, Steve
Scholars have expressed sustained interest in the social–emotional adjustment of gifted children, with conflicting views persisting: one that gifted students possess greater resiliency to environmental stress; the other that this population is more vulnerable. Capitalizing on the few case studies that examined adjustment among gifted students, the researcher conducted a cross-case study of two highly productive fourth-grade students at a K–12 public school. Data were collected throughout the course of a school year and included interviews with students and their parents. Findings included students' relying on strengths to cope with their surroundings and periodically isolating themselves.